2018
DOI: 10.24874/ti.2018.40.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 Nanoparticles Blended with Lubricating Oil on the Tribological Performance of the Journal Bearing

Abstract: This paper presents the performance analysis for plain and elliptical journal bearing operating with industrial lubricants. Titanium dioxide nanoparticle of size 40 nm is used as a lubricant additive to examine the performance of the bearing. Comparative analysis is carried out for three different lubricants with titanium dioxide (0.5% wt) nanoparticles. Performance of bearing is measured at speeds ranging from 500 r.p.m. to 1000 r.p.m. and at 1000 N load. The study of antiwear and antifriction properties for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Suryawanshi and Pattiwar [68] analyzed the performance of plain and elliptical journal bearing operating with industrial lubricants. Such bearings were lubricated by oil with TiO 2 nanoparticles with 40 nm in diameter.…”
Section: Lubricants With Tio 2 Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Suryawanshi and Pattiwar [68] analyzed the performance of plain and elliptical journal bearing operating with industrial lubricants. Such bearings were lubricated by oil with TiO 2 nanoparticles with 40 nm in diameter.…”
Section: Lubricants With Tio 2 Nanoparticlesmentioning
confidence: 99%
“…During studies carried out by Suryawanshi and Pattiwar [68], the TiO 2 nanoparticles were added to the lubricating oil at 0.5% wt., as such nanoparticles are synthetically steady. Hence, the chances of a reaction with base liquid and tribosurfaces were very low.…”
Section: Preparation Of Mixture Of Oil and Tio 2 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that adding specific percentage of different nanoparticles such as TiO 2 , Al 2 O 3 , CuO, etc. can significantly influence several aspects of journal bearing performance such as thermodynamic characteristics and tribological performance [20].…”
Section: Introductionmentioning
confidence: 99%
“…The performance parameters such as pressure distribution, frictional force, maximum pressure built up are increased in the elliptical bearing. 17…”
Section: Introductionmentioning
confidence: 99%